Analisis Makkiyah Dan Madaniyyah Dalam Konteks Penafsiran Al-Qur'an - Nafi’ Mambaul Hikmah Sholeh (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Makkiyah and Madaniyyah are the two main categories in the classification of Quranic suras based on the period of revelation. The Makkiyah suras refer to the revelations received by Prophet Muhammad before his migration to Medina, while the Madaniyyah suras refer to the revelations received after the migration. This distinction is not only chronological, but also reflects the social, political and spiritual context of the time, which influenced the message and style of the Quran. The analysis of Makkiyah and Madaniyyah in the context of Quranic interpretation serves to understand the deeper meaning, theme and message of Quranic verses. Makkiyah suras are generally characterized by a focus on monotheism, faith, and the threat and promise of the afterlife. The language style is more poetic, with shorter verses. In contrast, the Madaniyyah suras tend to address legal aspects and inter-community relations. The style is more narrative, with longer verses. In the context of interpretation, whether a surah is Makkiyah or Madaniyyah can help the mufassir (exegete) in interpreting verses and understanding their historical context, in this study, we explore the methods and approaches used in identifying Makkiyah and Madaniyyah surahs. Keywords: Al-Qur,an, Makkiyah, Madaniyyah, Interpretation